Automated test case generation for the Paxos single-decree protocol using a Coloured Petri Net model - Wang, Rui; Kristensen, Lars Michael; Meling, Hein; Stolz, Volker (Journal of logical and algebraic methods in programming, 2019)
Implementing test suites for distributed software systems is a complex and time-consuming task due to the number of test cases that need to be considered in order to obtain high coverage. We show how a formal Coloured Petri Net model can be used to automatically generate a suite of test cases for the Paxos distributed consensus protocol. The test cases cover both normal operation of the protocol as well as failure injection. To evaluate our model-based testing approach, we have implemented the Paxos protocol in the Go programming language using the quorum abstractions provided by the Gorums framework. Our experimental evaluation shows that we obtain high code coverage for our Paxos implementation using the automatically generated test cases.